II- from ecological recycling of Pd to greener sonogashira cross-coupling reactions. (15th April 2021) - Adler, Pauline; Dumas, Timothé; Deyris, Pierre-Alexandre; Petit, Eddy; Diliberto, Sébastien; Boulanger, Clotilde; Grison, Claude
Abstract: Based on a new process derived from biosorption technology that uses roots from aquatic and wetland plants ( Mentha aquatica, Eichhornia crassipes, Pistia stratiotes, Ludwigia peploides, Fallopia japonica), materials rich in lignin (pinecone, bark pine) and wastes rich in tannins (coffee grounds), we were able to prepare a new class of ecocatalyst, called Eco-Pd. The formed Eco-Pd are characterized via MP-AES and XRDP in the order to elucidate the chemical composition and the structure of the new formed materials. Interestingly, the presence of higher-oxidation-state palladium species, namely K2 PdCl6, is observed. We describe the use of this new generation of Eco-Pd for a green and sustainable Sonogashira reaction. The absence of copper, ligands, additives, a lower Pd loading (0.05 mol% - 0.1 mol%), the use of green solvents (glycerol/n-BuOH), and the use of biosourced Pd and base (Eco-Ca), are significant advantages of this approach. The combination TON/TOF (10 3 /250 h −1 ) can be advantageously compared with literature and demonstrates the remarkable practical utility of these new catalysts. Most importantly, the Eco-Pd can be easily recycled by biosorption and reused, that is another asset in terms of sustainable Chemistry.